2011
DOI: 10.1111/j.1751-1097.2010.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐generated Paramagnetic Intermediates in BLUF Domains

Abstract: Blue-light sensitive photoreceptory BLUF domains are flavoproteins, which regulate various, mostly stress-related processes in bacteria and eukaryotes. The photoreactivity of the flavin adenine dinucleotide (FAD) cofactor in three BLUF domains from Rhodobacter sphaeroides, Synechocystis sp. PCC 6803 and Escherichia coli have been studied at low temperature using time-resolved electron paramagnetic resonance. Photoinduced flavin triplet states and radical-pair species have been detected on a microsecond time sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 77 publications
2
20
0
Order By: Relevance
“…A comparable effect has been observed in the triplet state of a methionine mutant of the photoreceptor YcgF. 61 Continuous-Wave EPR Spectroscopy. Pulsed and continuous-wave paramagnetic electron resonance spectroscopy is a widely used sensitive method to detect radicals and other paramagnetic molecules.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…A comparable effect has been observed in the triplet state of a methionine mutant of the photoreceptor YcgF. 61 Continuous-Wave EPR Spectroscopy. Pulsed and continuous-wave paramagnetic electron resonance spectroscopy is a widely used sensitive method to detect radicals and other paramagnetic molecules.…”
supporting
confidence: 55%
“…59 Following the analysis outlined previously, 61 the spectra show a characteristic powder pattern centered around the g value of the flavin triplet state that is dependent on the two zero-field splitting parameters D and E and the populations p i with i = x, y, z of the three triplet sublevels. In general, all samples except Rf-LumP T50W show a trEPR signal that can be fully described by a flavin triplet state.…”
mentioning
confidence: 99%
“…The light-induced reaction produced various spectrally distinct radical pair difference spectra on the ultrafast time scale, which were assigned to FAD/Trp-8 radical pairs but might also correspond to a radical pair consisting of FAD and the semiconserved Trp-91. Using transient EPR spectroscopy, a strongly coupled radical pair was detected in this mutant, which was significantly different from the WT radical pair and decayed slightly slower (74). Because the Y8W mutation, however, rendered the BLUF photoreceptor non-functional and the radical pairs probably originate from the FAD triplet state rather than the singlet excited state, these findings are difficult to relate to WT and functional BLUF mutants directly.…”
Section: Discussionmentioning
confidence: 87%
“…Previously, we modulated the tyrosine redox partner by exchanging the phenolic side chain by an indole moiety using site-directed mutagenesis (44,74). Although the Slr1694-Y8W mutant was able to photoreduce the flavin to a radical state with high efficiency, no signaling state was formed, probably due to alterations in the flavin-coordinating hydrogen bond network involving Gln-50.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the removal of the conserved glutamine prevents signalling state formation [25], although a neutral flavin semiquinone is formed in the Slr1694 Q50A mutant that lives for a few nanoseconds (T. Mathes & R. Fudim 2011, unpublished data). By replacement of the phenol side chain by an indole (Y8W), which, in principle, should provide a similar chemical basis to both donate electrons and protons to the flavin-like tyrosine, we also observed the formation of a mixture of several flavin radical pair species, which however also did not yield the red-shifted signalling state [70,71]. These studies showed that not only light-induced PCET is required for BLUF photoactivation but also defined interactions between protein and flavin are necessary for the hydrogen bond switch to be facilitated.…”
Section: Ultrafast Structural Responses In Bluf Photoreceptors Upon Imentioning
confidence: 99%